Biosynthesis of AgNPs by B. maydis and its antifungal effect against Exserohilum turcicum. Issue 5 (4th April 2018) - Huang, Weidong; Fang, Xueliang; Wang, Hongdao; Chen, Fengchan; Duan, Haiming; Bi, Yaling; Yu, Haibing
Abstract : In the present study, Bipolaris maydis was used to synthesise silver nanoparticles (AgNPs). Several parameters that influence the synthesis of AgNPs such as fungus age, the concentration of Ag nitrate (AgNO3 ), and incubation time were explored to find the optimum synthesis condition. Furthermore, the antifungal activity of AgNPs against Exserohilum turcicum was determined by measuring inhibition zone diameter, colony formation, and conidia germination. The optimal biosynthesis system included fungus age of 7 days, 8 mM AgNO3, and an incubation time of 120 h. Under these conditions, synthesised NPs were near round, and the average particle size was about 21 nm. At the experiment, the diameter of the inhibition zone reached a maximum of 8 mM AgNO3 and 72 h. In addition, the inhibition rate of colony and conidia reached 83.39 and 100%, respectively, with 200 μg/ml AgNPs. The results offer a novel pathway for phytopathogen control and make it likely to develop new eco‐friendly antimicrobial.